Offshoring and Skill-Biased Technical Change in the Context of US Protectionism - Pablo Agnese; Jana Hromcová (Institute of Labor Economics (IZA), 2019)
We discuss the effects of offshoring on the labor market in a matching model with endogenous adjustment of educational skills. We carry out a comparative statics analysis and show that offshoring leads to a restructuring of the economy through skill-biased technical change (SBTC) where overall welfare is improved. In a policy exercise we show that, if offshoring were to be opposed by a protectionist agenda, labor market flexibility can bring about the same welfare gain. In addition, we offer an empirical analysis aimed at verifying the correlation be- tween offshoring and SBTC in US manufacturing industries in recent years. Our results show that different offshoring strategies affect SBTC differently. In particular, the evidence suggests that while high-skill offshoring strategies open the skill gap, low-skill offshoring strategies tend to work in the opposite direction.
Keywords: F66; J64; F16; F17; 330; offshoring; skills; skill-biased technical change